Identifying the need for specialized palliative care in adult cancer patients - Development and validation of a screening procedure based on proxy assessment by physicians and filter questions - Ostgathe, Christoph; Wendt, Kim N.; Heckel, Maria; Kurkowski, Sandra; Klein, Carsten; Krause, Stefan; Fuchs, Florian; Bayer, Christian M.; Stiel, Stephanie (BMC Cancer, 2019)
Background: One challenge in caring for cancer patients with incurable disease is the adequate identification of those in need for specialized palliative care (SPC). The study's aim was to validate an easy to use phenomenological screening tool. Methods: The German tool is based on the National Comprehensive Cancer Network (NCCN) Palliative Care guidelines and contains ten items in five domains that focus e.g. on diagnosis, functional status, complications, comorbidities, and palliative care relevant problems such as symptom management, distress, and support of family and team members. Sum score ranges from 0 to 14 (no need to great need). Assessment to identify SPC needs was done in university hospital wards between 1 and 08/2017 by health care professionals on admission of the patient if the disease was incurable and expected prognosis < 12 months. The Integrated Palliative Outcome Scale (IPOS, staff version), an outcome assessment instrument for palliative care that consists of ten items, served as external criterion; in sub samples inter-rater/test-retest were performed. Results: Data from 208 patients with incurable disease and life expectancy < 12 months (54.8% female; average age 63.5 years, range 21-96) were assessed using the tool. The tool has good convergent validity; the correlation between the sum scores of IPOS and our tool showed a significant and substantial effect. The sum score was independent of the patient's age, gender and primary diagnosis. Patients who already were in contact with SPC had significantly higher screening scores than patients without. With a cut point of ≥ 5, 80.8% of the screened patients were in need for SPC. Cronbach's alpha was α =.600. Rater agreement (inter-rater, test-retest) varied between single items. Correlation coefficients showed significant substantial effects. Conclusions: This is the first validation of a screening procedure in German language identifying SPC needs of adult patients with advanced cancer and the first using filter questions as a pre-screening. Proxy assessment of SPC needs by physicians in cancer care settings is feasible and the suggested tool presents a valid instrument to trigger a PC consultation. Trial registration: The study was not registered.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cancer; Delivery of health care; Needs assessment; Palliative care; Psychometric properties